Longitudinal Genomic Evolution of Conventional Papillary Thyroid Cancer With Brain Metastasis - Luo, Han; Liao, Xue; Qin, Yun; Hou, Qianqian; Xue, Zhinan; Liu, Yang; Shen, Feiyang; Wang, Yuelan; Jiang, Yong; Song, Linlin; Chen, Haining; Zhang, Lingyun; et al. (Frontiers in Oncology, 2021)
Background: Brain metastasis is extremely rare but predicts dismal prognosis in papillary thyroid cancer (PTC). Dynamic evaluation of stepwise metastatic lesions was barely conducted to identify the longitudinal genomic evolution of brain metastasis in PTC. Method: Chronologically resected specimen was analyzed by whole exome sequencing, including 4 metastatic lymph nodes (lyn 1-4) and brain metastasis lesion (BM). Phylogenetic tree was reconstructed to infer the metastatic pattern and the potential functional mutations. Results: Contrasting with lyn1, ipsilateral metastatic lesions (lyn2-4 and BM) with shared biallelic mutations of TSC2 indicated different genetic originations from multifocal tumors. Lyn 3/4, particularly lyn4 exhibited high genetic similarity with BM. Besides the similar mutational compositions and signatures, shared functional mutations (CDK4 R24C, TP53 R342*) were observed in lyn3/4 and BM. Frequencies of these mutations gradually increase along with the metastasis progression. Consistently, TP53 knockout and CDK4R24C introduction in PTC cells significantly decreased radioiodine uptake and increased metastatic ability. Conclusion: Genomic mutations in CDK4 and TP53 during the tumor evolution may contribute to the lymph node and brain metastasis of PTC.